Geographical assessment of primary education services in the city of medhatiya in the province of Babylon for the year 2022 (Journal of the College of Basic Education, 2024)
The research aims to evaluate the educational competence of primary schools (governmental and private) in the center of the sub-district in Babel Governorate, as the city of Medhatiah is distinguished by the presence of a number of primary schools, which reached (26) schools (governmental / private) distributed throughout the city, as for the number of educational staff The number of students reached (593) teachers, and the number of students reached (12204) male / female students, while the number of academic divisions reached (316) divisions. And it became clear through evaluating the data that there is a defect and a clear lack of violation of the approved standard, as it was found that the pupil / school indicator. In (20) schools are higher than the standard, while schools that scored less than the approved standard are (6) schools. As for the pupil / teacher index, and this indicator (20 pupils / teacher) was adopted in order to measure the efficiency of the educational service in the city, as it became clear that the general average for this indicator reached (21) pupils / teacher, and this indicates a mismatch with the approved Iraqi standard, schools The numbers that scored higher than the standard amounted to (14) schools, and the schools that scored less than the standard amounted to (8) schools, while the schools that took an index in conformity with the Iraqi standard reached (4) schools. And the pupil / division index. When applying this indicator, we notice that there is no match with the approved Iraqi standard (30 students / divisions), as it was found that the number of schools that registered higher than the approved standard amounted to (21) schools and the schools that registered less than the standard are (4) schools. As for the statistical analysis of school sites in the GIS programs, it shows that there is a random distribution of the sites of the original schools in the study area. Regular distribution and weighted according to neighborhoods and population were not taken into account in it. The research concluded that there is no application of the standard and this is due to the scarcity of school buildings and the lack of educational staff, not to mention the presence of large numbers that have not enrolled in schools due to the economic situation and education requirements. The research recommends the necessity of intensifying official and popular efforts to increase the number of school buildings to eliminate duplication and employ more cadres than the existing one. Official and popular education on enrollment in education because of the basis for the renaissance of the region and the nation. It is also recommended to follow technical methods in choosing the appropriate site through geographic information systems based on the required standards and weights.